Personality Disorders: Self-Learning Module (Out of Print) - Martin Klapheke (Association of American Medical Colleges, 2012)
Abstract This resource is a self-learning module (SLM) intended to provide an alternative clinical experience for third-year medical students who do not encounter a patient with personality disorders during their psychiatry clerkship. SLMs have the potential to improve understanding, facilitate learning, and possibly improve medical students' test performance. This current module is part of a collaborative, multi-institutional effort to develop web-based SLMs with a consistent pedagogical approach. This SLM is not meant to replace actual clinical experience but, rather, to provide a meaningful learning experience if the ideal of direct exposure to the desired clinical condition is not possible. This SLM has been implemented in the University of Central Florida College of Medicine psychiatry clerkship didactics. Anonymous verbal and written feedback from medical students, as well as from faculty, has been positive.